Non symmetric Rosenblatt process over a compact. Issue 23 (2nd December 2021) - Araya, Héctor; Garzón, Johanna; Roa, Tania
Abstract: In this short note, we give the representation of the non symmetric Rosenblatt process as a Wiener–Itô multiple integral with respect to the Brownian motion on a finite interval. Based on this representation, we obtain a least square-type estimator for an unknown parameter of the drift coefficient of a simple model driven by the non symmetric Rosenblatt process.